Sub‐tephra archaeology and geochemistry at La Arenera, Managua, Nicaragua form a record of human activity before the Asososca Maar eruption of 2130 BP. Issue 5 (22nd March 2019) - Neff, Hector; Lange, Frederick W.; Kooistra, Marty; Caro, Carlos; Rankle, Chad
Abstract: We recently investigated an occupational surface that lies at the base of a deep deposit of volcanic sand emplaced approximately 2130 years ago in what is now a western suburb of Managua, Nicaragua. LA4, an area of 25 × 18 meters from which overlying sand had been removed by quarrying, was cleaned so that features and artifacts could be point plotted and sediments from the pre‐eruption surface could be sampled. Portable x‐ray fluorescence analysis of surface sediments detected patterns of elemental enrichment that are interpretable as signals of pre‐eruption human activities. The geochemical data combined with feature and artifact distributions support several inferences about how people were using the space on the eve of the 2130 BP volcanic event. A small test excavation confirmed the presence of a shallow but moderately dense primary refuse deposit containing sparse but varied faunal remains, including marine species. The ubiquity of artifact scatters on other exposures of the sub‐tephra surface suggests that the site covers at least 96 hectares, and we speculate that more intact and denser deposits than LA4, possibly including structures and agricultural features, may eventually be encountered.